2019
DOI: 10.3389/fnbeh.2019.00232
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate in Salience Network Predicts BOLD Response in Default Mode Network During Salience Processing

Abstract: BackgroundBrain investigations identified salience network (SN) comprising the dorsal Anterior Cingulate Cortex (dACC) and the Anterior Insula (AI). Magnetic resonance spectroscopy (MRS) studies revealed the link between the glutamate concentration in the ACC and alterations in attentional scope. Hence, we investigated whether glutamate concentration in the dACC modulates brain response during salience processing.MethodsTwenty-seven healthy subjects (12♀, 15♁) provided both STEAM MRS at 7T measuring glutamate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Overbeek et al ( 34 ) observed ACC glutamate levels were positively associated with NBR in a cluster spanning from the PCC and precuneus to the occipital cortex and cerebellum. Von During et al ( 45 ) also found that ACC glutamate levels were positively associated with NBR in the PCC, with higher glutamate predicting higher deactivation of this area in response to a variety of stimuli. Neural activity in a variety of other regions were also negatively correlated with ACC glutamate levels in this study (see Table 4 ).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Overbeek et al ( 34 ) observed ACC glutamate levels were positively associated with NBR in a cluster spanning from the PCC and precuneus to the occipital cortex and cerebellum. Von During et al ( 45 ) also found that ACC glutamate levels were positively associated with NBR in the PCC, with higher glutamate predicting higher deactivation of this area in response to a variety of stimuli. Neural activity in a variety of other regions were also negatively correlated with ACC glutamate levels in this study (see Table 4 ).…”
Section: Resultsmentioning
confidence: 94%
“…supragenual ACC Glx levels, however, were not associated with pgACC activation during the empathy task. ACC glutamate levels were also studied in conjunction to neural activity during a salience processing task using emotional and erotic pictures ( 45 ). Activation in the sgACC related to unexpectedness of emotional pictures displayed a negative correlation with glutamate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have found that subanesthetic doses of the NMDA receptor antagonist ketamine induce psychoses-like symptoms in healthy volunteers ( Krystal et al, 1994 ; Malhotra et al, 1996 ). Ketamine influences memory ( Malhotra et al, 1996 ; Morgan and Curran, 2006 ) and modulates attentional processes ( Oranje et al, 2000 ; Watson et al, 2009 ; Gunduz-Bruce et al, 2012 ; Fuchs et al, 2015 ; von Düring et al, 2019 ; but see Morgan et al, 2004 ; van Wageningen et al, 2010 ). For example, Fuchs et al (2015) investigated the influence of ketamine on top-down attentional control using a visual cueing paradigm.…”
Section: Neuromodulatorsmentioning
confidence: 99%